Refinement of eutectic structure and precipitates of Cu–20Ag alloy due to Y microalloying - Zhichao Wang; Chaomin Zhang; Shaolin Li; Kexing Song; Yanjun Zhou; Yahui Liu; Junjie Sun; Jun Cao (Journal of Materials Research and Technology)
Copper-silver alloy rod with high mechanical properties and stable conductivity are the key materials for the preparation of microfilaments used in endoscopy and other medical fields. In this paper, the microstructure of Cu–20Ag rod was regulated by adding trace rare earth Y in order to improve the comprehensive performance of copper-silver alloy further. and studies the distribution and existence of rare earth Y as well as the influence on the performance of copper-silver alloy rod billet. The results of research show that: rare earth Y mainly exists in the branching nodes of the eutectic organization, so that the alloy in the solidification of constitutional supercooling increases, thus refining the eutectic structure, and make it uniformly distributed. After addition of 0.01 wt%Y, Cu4Y was precipitated in the eutectic structure of the rod. After adding 0.03 wt%Y, the precipitates types increased to trace intermetallic compound AgY and nanoparticles Cu4Y. The increase of the interface between eutectic structure and Cu matrix decreases the electron scattering probability. This is the main factor to lead to the decrease of electrical conductivity. The precipitation hardening of precipitated phase and the increase of interface between eutectic structure and Cu matrix are the main factors for the increase of tensile strength of bar billet. The main factor of the decrease in the conductivity of rod billet is the increase of Ag phase dissolved in eutectic structure and the interface between eutectic structure and Cu matrix.